Turkey: Mediator or Player in the Confrontation Between Russia and Ukraine? - Hovhannisyan , Anush (History and Culture, 2023)
Turkey manages to be a strategic partner of Ukraine and Russia at the same time, despite the fact that these countries are in a state of actual war with each other. Turkey consistently condemns Russia's annexation of Crimea and supports future NATO membership for Ukraine․ Ankara verbally condemned the Russian invasion almost immediately after February 24, but did not join any sanctions against Russia. But from the very beginning, it tried in every possible way to become the main mediator in organizing peace negotiations between Moscow and Kyiv.Ankara takes the most advantageous position for itself, trying to benefit from someone else's conflict. At the same time, Turkey is trying to increase its political influence, acting as a mediator in the negotiations, as a “great peacemaker”. Turkey positions itself as a true regional leader, and in its relations with both Russia and Ukraine, it tries to follow the ancient principle of "divide and rule." Recep Tayyip Erdogan seeks everywhere to take advantage of Russia's weaknesses and increase his influence - or rather, in the understanding of the current Turkish authorities, “to return the influence that was lost in the 19th and early 20th centuries”.Why Ankara is behaving this way and what are the personal interests of Turkish President Recep Erdogan in this war - these questions will be analyzed in this article.
Keywords: Russian-Ukrainian conflict; annexation of Crimea; Turkey; Erdogan; Turkish-Ukrainian relations; Russian-Turkish; sanctions; peace mediation.